Research Toward a Heterogeneously Integrated InGaN Laser on Silicon. Issue 7 (29th December 2019) - Kamei, Toshihiro; Kamikawa, Takeshi; Araki, Masahiro; DenBaars, Steven P.; Nakamura, Shuji; Bowers, John E.
Abstract : A heterogeneously integrated InGaN laser diode (LD) on Si is proposed as a path toward visible wavelength photonic integrated circuits (PICs) on Si. Herein, InGaN films are vertically stacked on a TiO2 waveguide (WG) fabricated on a Si wafer by bonding. In the light propagation direction, it is composed of a hybrid InGaN/TiO2 section, a TiO2 WG, an adiabatic taper, and mirrors that can form a cavity. As the refractive index of GaN is well matched with that of TiO2, the optical transverse mode extends to both the GaN and TiO2 in a hybrid mode. Modes between a hybrid InGaN/TiO2 and a pure TiO2 WG can transfer with an adiabatic taper structure. The coupling loss is calculated to be less than 0.5 dB with fairly short taper length of 78 μm and tip width of 200 nm. GaN substrate removal and bonding are critical fabrication steps of this LD and PIC. The substrate removal is successfully done by photoelectrochemical etching. Although direct bonding of GaN wafers with thermal oxide on Si is successful, GaN epitaxial wafers are more difficult. An implication and remedy of this is discussed in terms of surface roughness of GaN epitaxial film. Abstract : A heterogeneously integrated InGaN laser diode is proposed, wherein InGaN films are vertically stacked on a TiO2 waveguide fabricated on a Si wafer by bonding. The optical transverse mode extends to both the GaN and TiO2 in a hybrid mode, facilitating design and fabrication of an adiabatic taper structure. GaN substrate removal and bonding are also presented and discussed.